EFECTOS DE LA APLICACIÓN DE LA SALVAGUARDIAS EN EL SECTOR COMERCIAL EN LA CIUDAD DE HUAQUILLAS AÑO 2015 - Ordoñez Bravo, Steven (2015)
This research was conducted in order to analyze what have been the effects that caused the application of safeguards in the commercial sector of the city of Huaquillas respescto tariffs have been applied following the imposition of this measure safeguards, identify what was the cause and the legal basis on which the imposition of this measure in Ecuador and the manner in which the appreciation of the dollar occurred took place and how that affected sales traders in this sector and which governed these tariff rates. In order to obtain the information presented in this study, secondary sources were consulted literature which served as basis for the understanding of the problem and primary sources were applied as the survey and interviews which allow information directly, to depth knowledge of the effects that caused the problem, applied research was descriptive research and qualitative and quantitative type because tabulated and graphically presented the results obtained with a brief analysis of the data found. As a result it was possible to identify that as 75% of the survey sample is represented by traders in the border area of Huaquillas, it states that the local economy of the southern border area of Huaquillas is under a process of change and decrease due to new measures imposed by the Government and that the decline in dollar sales totaled about mostly between about $ 4000 and $ 8000 US dollars per year.